Danny Dorling and Stuart Gietel-Basten (2018). Why Demography Matters. Oxford, UK: Policy Press - Chełchowska, Milena (Studia Demograficzne, 2021)
The book entitled Why Demography Matters (written by Danny Dorling and Stuart Gietel-Basten) describes the role of demography in shaping humans’ perception of the world. It tries to highlight the excesses of competence, too hasty conclusions, and mistakes in the assessment of the world around us and in visions of what the future of mankind will look like from the demographic point of view.